228 NICOTINE PROMOTES MATRIX EXPRESSION IN ENDOTHELIAL CELLS THROUGH a7 NICOTINIC ACETYLCHOLINE RECEPTOR-MEDIATED SIGNALS. (1st January 2006) - Gaffar, M.; Ritzenthaler, J.; Rivera, H.; Roser-Page, S.; Hart, C. M.; Roman, J.
Abstract : Pulmonary hypertension (PHTN) is a frequent complication in the natural history of tobacco-related chronic obstructive pulmonary disease, but the pathogenesis of PHTN in the setting of tobacco exposure is not well understood. The traditional view is that PHTN occurs secondary to a loss of the pulmonary vascular bed through destruction of alveolar septae in emphysema; however, other mechanisms are likely to contribute. We hypothesize that nicotine (one component of tobacco smoke) directly promotes vascular remodeling by stimulating pulmonary endothelial cells to express matrix genes through effects on a7 nicotinic acetylcholine receptors (nAChRs). Consistent with this hypothesis, we demonstrated the expression of a7 nAChRs in human lung endothelial cells. Upon exposure to nicotine, the endothelial cells showed accumulation of mRNA encoding for fibronectin, a matrix glycoprotein highly expressed in chronic lung disease that has been implicated in tissue injury and repair. This effect was followed by fibronectin protein production and was blocked by pretreatment with a-bungarotoxin, a specific inhibitor of a7 nAChR function. To evaluate the relevance of our findings to the lung vasculature, we examined the lungs of animals provided nicotine in their drinking water (100 μg/mL, 90 days) using immunohistochemistry. Analysis of the lung histology revealed increased fibronectin deposition within pulmonary vascular walls. Altogether, these data suggest that tobacco components (ie, nicotine) promote lung endothelial cell expression of matrix glycoproteins like fibronectin, thereby promoting vascular remodeling.